One day in the woods - George, Jean Craighead, 1919-; Allen, Gary (Gary J.) (New York : Crowell, 1988)
Rebecca discovers many things about plant and animal life when she spends the day in Teatown Woods in the Hudson Highlands of New York looking for the ovenbird.
Includes index.
Bibliography: p. 39.
Wilson's Children
Book Links (A.L.A.)
Booklist
4.5
Keywords: Forest ecology -- New York (State) -- Teatown Woods -- Juvenile literature; Ovenbird -- New York (State) -- Teatown Woods -- Juvenile literature; Forest birds -- New York (State) -- Teatown Woods -- Juvenile literature; Birds -- New York (State) -- Teatown Woods -- Juvenile literature; Teatown Woods (N.Y.) -- Juvenile literature; Forests and forestry -- New York (State); Forest birds; Natural history; Forests and forestry -- New York (State); Natural history; Forest ecology